P187 Acute NIV: Factors associated with clinical outcomes at a central London teaching hospital. (12th November 2019) - Mackay, E; Cho, P; Papamanoli, A; Burney, A; Lyall, R; Patel, A; Metaxa, V; Lee, KK
Abstract : Introduction: Non-invasive ventilation can be an effective treatment for acute hypercapnic respiratory failure, but national audits have consistently demonstrated poorer clinical outcomes than expected. Several potential factors have been identified as being associated with poor outcome. This study was conducted to assess the impact of factors on the clinical outcomes of patients commenced on acute NIV at a central London teaching hospital. Methods: A case record review was carried out for all patients treated with acute NIV for hypercapnic respiratory failure in a 12-month period. Patients already being treated with home ventilation were excluded. Clinical outcomes assessed were: NIV success (as defined by BTS criteria) and in-hospital mortality. Lateness of NIV initiation (<24 hrs vs >24 hrs), location of instigation (ED vs non-ED), background of COPD (presence vs absence), presence of consolidation (presence vs absence) and initial pH (<7.26 vs >7.26) were recorded and their relationships with the clinical outcomes assessed. Results: 141 Acute NIV episodes were identified, of which 75 had complete records available for analysis (mean±SD age 69±10 years, 56% female). Mean±SD initial pH was 7.22±0.08, pCO2 10.8±2.4 kPa and HCO3- 31.2±6.0 mEq.L-1. Overall NIV success rate was 72% and in-hospital mortality 22.7% (vs 34.6% nationally). 69% were admitted to ICU. 12% were intubated (vs 5% nationally). pH<7.26 was associated with increased mortality (OR (95% CI) 5.09 (1.09–23.82); p=0.039). None of the other factors assessed were associated with statistically significantly increased mortality or NIV success (p=0.073–0.999). There was no significant difference in mortality between those who admitted to ITU vs not admitted (P=0.766). Conclusions: In this single centre study, NIV success and in-hospital mortality of patients treated with acute NIV compared favourably with national data. pH<7.26 was associated with significantly higher mortality. Further study is required to assess the interactions between these factors and their impact on patient outcomes.